2018
DOI: 10.1186/s12933-017-0654-z
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial

Abstract: Background and aimsSodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.Materials and methodsIn a prospective double blind, placebo controlled, cross-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 41 publications
3
104
0
3
Order By: Relevance
“…It is therefore noteworthy that SGLT2 inhibitors reduce intracellular sodium in cardiomyocytes, an action that is independent of glucose . This effect has been confirmed in the clinical setting and has been proposed to underlie the cardioprotective effect of these drugs seen in randomized controlled trials …”
Section: Novel Mechanisms By Which Sglt2 Inhibitors May Promote Cardimentioning
confidence: 78%
“…It is therefore noteworthy that SGLT2 inhibitors reduce intracellular sodium in cardiomyocytes, an action that is independent of glucose . This effect has been confirmed in the clinical setting and has been proposed to underlie the cardioprotective effect of these drugs seen in randomized controlled trials …”
Section: Novel Mechanisms By Which Sglt2 Inhibitors May Promote Cardimentioning
confidence: 78%
“…As SGK1 activity may modulate NHE activity through Aktmediated signaling, these results suggest that empagliflozin could restore myocardial [Na + ] c in a sustained manner (55). Examinations using 23 Na + magnetic resonance imaging revealed that the tissue Na + content in diabetic patients was markedly reduced by treatment with dapagliflozin (56). An in silico docking study demonstrated that three SGLT2 inhibitors, empagliflozin, dapagliflozin, and canagliflozin, showed high binding affinity with the extracellular Na + -binding site of NHE (57).…”
Section: Sglt2 Inhibitors Promote Sodium Metabolism-mediated Cardioprmentioning
confidence: 85%
“…Diuretic treatment of patients with acute heart failure reduces tissue Na ϩ by 20 -26% (15). A recent clinical trial showed a modest decrease in skin Na (5.8%) and no change in muscle Na ϩ in diabetic patients treated with dapagliflozin for 6 wk (18). It is possible that reduced tissue osmolality due to lowering of glucose levels over 6 wk contributed to this response.…”
Section: Discussionmentioning
confidence: 99%